Smart Phone Based Billing System for Android Users - Renuka B S, Sachin T M, Darshan Gowda M C (International Journal of Advanced Science and Technology, 2020)
Shopping malls or Super markets are the places where the people can get their daily necessities ranging from food products, cloths to electronic appliances. It is common to see a huge rush in these places where there is a lot of offers in the festive season. In today’s generation everything the society uses getting automated and also each and every minute is important in their life. So, we automate in the area of shopping which helps in reducing the time consumed during shopping. Our system “SMARTPHONE BASED BILLING SYSTEM FOR ANDROID USERS” uses barcodes of the products in the shopping malls or in the supermarkets as it is unique for every product. In-built Barcode scanner is developed using mobile’s rear camera which scans the product barcode and decodes into product ID using this the price and name of the product is fetched in database. It shows the total amount to be paid by the customer can pay by using UPI payments or by cash. By using this facility, customers can save their precious time without standing in the Queue for long time and can utilize this time for other things.